Cognitive ability is associated with changes in the functional organization of the cognitive control brain network. Issue 12 (23rd August 2018) - A. Breukelaar, Isabella; Williams, Leanne M.; Antees, Cassandra; Grieve, Stuart M.; Foster, Sheryl L.; Gomes, Lavier; Korgaonkar, Mayuresh S.
Abstract: Cognitive control is one of the most important skills in day‐to‐day social and intellectual functioning but we are yet to understand the neural basis of the group of behaviors required to carry this out. Here, we probed changes over time in the brain network associated with cognitive control (the dorsolateral prefrontal cortex, the dorsal posterior parietal cortex, and the dorsal anterior cingulate cortex) using both behavioral assays and functional brain imaging during a selective working memory task in 69 healthy participants within the age range 18–38 years (mean: 25, SD : ±6), assessed twice, 2 years apart. We aimed to explore the relationship of changing network activation and connectivity with behavioral tasks associated with cognitive control in this otherwise neurodevelopmentally stable group. We found that increased connectivity between frontoparietal cognitive control network regions during the working memory task was associated with improved memory and executive functions over the 2‐year period and that this association was not impacted by age, gender, or baseline performance. These results provide evidence that changes in the functional organization of the cognitive control brain network occur despite the absence of neurodevelopment, aging or targeted cognitive training effects, and could modulate cognitive performance in early to mid‐adulthood. Understanding how and why this change is occurring could provide insights into the mechanisms through which cognitive control ability is cultivated over time. This could aid in the development of interventions in cases where cognitive control is impaired.